PENAMBAHAN PELARUT ORGANIK PADA MEDIA UNTUK HIDROLISIS ENZIMATIK MINYAK IKAN MENGGUNAKAN LIPASE DARI Aspergillus niger - Sapta Raharja, Ono Suparno, Djumali Mangunwidjaja,Alamanda Herdiyani Teni Oktavia, Zulfatun Najah TI (Jurnal Teknologi Industri Pertanian, 2012)
Fish oil is one of important fatty acid sources that contains Omega-3 polyunsaturated fatty acid such as eicosapentanoic acid (EPA) and docosahexanoic acid (DHA).Omega-3 fatty acid in acylglycerol form (monoester) is considered better as food chemical form because it is digested easily by human digestive system. In this research, monoester was produced using Aspergillus niger lipase which cut the acylglycerol chain in the sn (1) and (3). Organic solvent especially hydrophobic solvent was used in the hydrolysis to increase the catalytic activity of the enzyme. The hydrophobic solvent used in this research had hydrophobicities between 2 until 4, such as toluene, hexane, and heptane. The objective of this research was to determine temperature, pH, and percentage of water added which produce the highest degree of hydrolysis in the presence of organic solvent. The correlation between the yield and the amount of omega-3 was also investigated. The variables used were temperature (25-65oC), pH (5-9) and water addition (1-5%V/V). In the toluene media, the highest degree of enzymatic hydrolysis reached 15.69% at 45oC, pH 5, and water addition of 1%V/V. In the hexane media, it reached 75.12% at 45oC, pH 5, and water addition of 5%V/V, and in the presence of heptane, it reached 23.94% at 25oC, pH5, and water addition of 1%V/V. Meanwhile, in the presence of toluene, it showed 3, 01% of total omega-3 that all of them was EPA. In the hexane media, total omega-3 was 21.93% with EPA amount of 17.75% and DHA of 1.21% and in the heptane media, total omega-3 was 12.1% with amount of EPA of 10.23%, and DHA of 1.87%. According to degree of hydrolysis, it can be concluded that hexane gave the best result for the enzymatic hydrolysis of fish oil by the lipase with addition of organic solvent.Keywords: fish oil, lipase, organic solvent, Omega-3,EPA, DHA